Kirkpatrick-Baez mirrors commissioning for coherent scattering and imaging endstation at SXFEL - Tong, Yajun; Fan, Jiadong; Nie, Yonggan; Guo, Zhi; Gao, Zichen; Yuan, Xinye; He, Bo; Chen, Jiahua; Zhang, Difei; Luan, Hui; Zhang, Jianhua; Lu, Donghao; et al. (Frontiers in Physics, 2022)
Shanghai Soft X-ray Free-Electron Laser(SXFEL) is the first X-ray free-electron laser facility in China. The initial commissioning of the beamline was carried out in May 2021. Herein, we present a status report and excellent results obtained during the early commissioning of Kirkpatrick-Baez (KB) mirrors for the Coherent Scattering and Imaging (CSI) endstation, including three types of diagnostics. A bright X-ray focal spot size of less than 3 μm was achieved by using edge-scan and silicon ablation imprint measurements. In order to confirm the spot size, attenuation beam and full beam are used respectively for these two measurement methods.